Literacia midiática e juventude: caminhos para a formação de cidadãos políticos no combate à desinformação - Portas, Isabela Afonso (2023)
Given the intense information flow, Post-Truth and the constant circulation of fake news, especially related to politics, this research’s main objective is to investigate how the consumption, access, evaluation and production of media by high school students influence their education and acting as a political citizen in the struggle against misinformation. For that, a qualitative approach was carried out with the aid of a bibliographical reference in view of the theoretical contributions referring to consumption, politics, misinformation, youth and media literacy. After this theorical research, in-depth episodic interviews were conducted with 16 high school students from public and private schools in the city of São Paulo. From the data collected, discussions and results were presented around the pillars of access, evaluation and creation, skills considered necessary for media literacy, which show how the consumption and production of media by the interviewees, and their criticality in this regard, interferes in how they exercise citizenship. Among the main findings of the research is the search for information via Google, the belief in few communication vehicles about politics, the concern of young people about checking information, the fear of taking a political position on the internet, the commitment of students regarding to mobilizations on social networks about causes they believe in, as well as a perspective on the importance of learning about the media at school and, at the same time, having a lack of school support for this.